The Impact of Agricultural Machinery Utilization on Production Efficiency and Productivity: A Case Study in Curahwelut Village, Ajung, Jember Regency - Rizky, Dian; Putra, Mohammad Edwinsyah Yanuan; Maghfiroh, Canggih Nailil (Politeknik Negeri Jember, 2025)
This study examines the economic impact of agricultural mechanization on smallholder rice and maize farmers in Curahwelut Village, East Java, Indonesia. Agricultural machinery (alsintan) offers a strategic solution to address labor shortages, rising production costs, and inefficiencies in farm operations. The research employs a quantitative case study approach involving ten purposively selected farmers, all of whom operate on rented land and utilize mechanized equipment at different production stages. Data were collected through structured interviews and analyzed using financial modeling, correlation, and regression techniques. Results show that mechanization enhances productivity, reduces physical labor, and contributes positively to farm profitability. All respondents achieved positive profits, with revenue and net cash flow directly correlated to investment in machinery. Break-even point (BEP), Net Present Value (NPV), Internal Rate of Return (IRR), and Profitability Index (PI) analyses confirm the economic feasibility of mechanization, with all farmers exceeding BEP thresholds. Regression analysis demonstrates a strong positive relationship between total cost and revenue (R² = 0.749), indicating that greater input investment yields higher returns. However, structural challenges such as insecure land tenure and aging farmer demographics remain barriers to broader adoption. Findings highlight the need for supportive policies that expand access to credit, improve technology distribution, and promote gender and youth inclusion. Mechanization, when effectively managed, enhances financial sustainability and contributes to rural economic development. This research underscores the importance of tailored mechanization strategies to improve the livelihoods of smallholder farmers in Indonesia.